Rf-sputtering deposition of nano-crystalline zirconia thin films with high transparency - Yildiz, Koksal; Akgul, Unal; Coskun, Burhan; Atici, Yusuf (Elsevier Science Bv, 2013)
Zirconia thin film was deposited on a microscope slide substrate by rf-sputtering. The surface morphology and elemental composition of the film were characterized by SEM and EDX. SEM images showed that the surface morphology of the film consists of spherical-like grains, grain agglomerates and micro voids. EDX experiments showed that the film is composed of 32.82 at% Zr and 67.18 at% O. The microstructure of the film was also investigated by TEM. It was found that the film has poly crystalline grains with nano-sized and different orientations. A study of lattice image for the film was done by HRTEM. The d(hkl) values were evaluated. Defects and lattice distortions were seen. The optical properties of the film showed that its average optical transmittance in the visible region is high (similar to 84%) and the values of E-g and E-u, are similar to 4.05 eV and similar to 0.446 eV, respectively. (C) 2012 Elsevier B.V. All rights reserved.
Keywords: Zirconia; Thin films; Sputtering; Microstructure; Optical properties